The World Bank economic review - World Bank (Washington,D.C World Bank, 1994)
WB elibrary": "The World Bank Economic Review is a professional journal that disseminates research sponsored by the World Bank and other institutions. The journal is meant to inform policy analysis and choice for international readers, including economists and social scientists in government, business, international agencies, universities, and development research institutions. The Review provides the best and most current research in the field of quantitative development policy analysis, with an emphasis on policy relevance and the operational aspects of economics. It is intended for readers familiar with economic theory and analysis but not necessarily proficient in advanced mathematical or econometric techniques. Articles illustrate how professional research can shed light on policy choices, and the material comes from work conducted by World Bank staff and consultants and by outside researchers"
published 3 / year (January, July and September) Full text articles are availabe from JSTOR
Keywords: Economic development; ECONOMIC DEVELOPMENT; ECONOMIC POLICY; ECONOMIC CONDITIONS; DEVELOPING COUNTRIES; PERIODICALS